Exploring risk patterns for incident ischemic stroke during more than a decade of follow-up: A survival tree analysis. (August 2017) - Parizadeh, Donna; Ramezankhani, Azra; Momenan, Amir Abbas; Azizi, Fereidoun; Hadaegh, Farzad
Highlights: Using survival tree analysis, risk patterns for ischemic stroke could be identified, based on the interactions between independent risk factors. Age, diastolic blood pressure, waist circumference and GFR interacted with each other in predicting the risk of ischemic stroke. The association of diastolic blood pressure with ischemic stroke increased in the presence of abdominal obesity or chronic kidney disease. Higher wrist circumference was associated with lower risk of ischemic stroke. Abstract: Background and purpose: The burden of stroke is increasing in low to middle income countries. Identifying risk patterns for ischemic stroke (IS) can help develop individualized preventive measures for at risk populations. Methods: The study population included 3088 Iranian subjects (1426 men) aged ≥50 years, free of cardiovascular diseases at baseline. The risk factors for ischemic stroke were identified by multivariate Cox analysis. A survival tree model was used to explore interactions between risk factors. Results: During 12 years of follow-up, 106 cases of IS occurred. Age (hazard ratio (HR): 1.08), male gender (HR: 1.69), diastolic blood pressure (DBP) (HR: 1.04), fasting plasma glucose (HR: 1.10), waist circumference (WC) (HR: 1.03) and smoking (HR: 1.96), were associated with increased risk and estimated glomerular filtration rate (eGFR) (HR: 0.97) and wrist circumference (HR: 0.68) decreased the risk of IS (all P -values <0.05). The survival tree identified six risk patterns. The highest and lowest risks were related to subjects ≥60.5 years with DBP ≥100 mmHg and subjects <60.5 years with DBP<97 mmHg, respectively. In subjects ≥60.5 years with DBP <100 mmHg, risk of ischemic stroke was determined by WC ≥96.5 cm or (eGFR) <60.87 ml/min/1.73 m 2 . Conclusion: By applying survival tree as a complementary method to the conventional Cox-analysis, for the first time, we identified risk patterns of ischemic stroke and explored the interactions between risk factors of the disease. DBP was the most important predictor of ischemic stroke in middle-aged and old subjects. In elderly subjects with DBP <100 mmHg, abdominal obesity was associated with high risk; however, among non-obese subjects, kidney dysfunction increased the risk of ischemic stroke. Wrist circumference was reported as a novel predictor.